Effect of Ciprofloxacin-Loaded Niosomes on Escherichia coli and Staphylococcus aureus Biofilm Formation - Linda Maurizi; Jacopo Forte; Maria Grazia Ammendolia; Patrizia Nadia Hanieh; Antonietta Lucia Conte; Michela Relucenti; Orlando Donfrancesco; Caterina Ricci; Federica Rinaldi; Carlotta Marianecci; Maria Carafa; Catia Longhi (MDPI AG, 2022)
Infections caused by bacterial biofilms represent a global health problem, causing considerable patient morbidity and mortality in addition to an economic burden. Escherichia coli, Staphylococcus aureus, and other medically relevant bacterial strains colonize clinical surfaces and medical devices via biofilm in which bacterial cells are protected from the action of the immune system, disinfectants, and antibiotics. Several approaches have been investigated to inhibit and disperse bacterial biofilms, and the use of drug delivery could represent a fascinating strategy. Ciprofloxacin (CIP), which belongs to the class of fluoroquinolones, has been extensively used against various bacterial infections, and its loading in nanocarriers, such as niosomes, could support the CIP antibiofilm activity. Niosomes, composed of two surfactants (Tween 85 and Span 80) without the presence of cholesterol, are prepared and characterized considering the following features: hydrodynamic diameter, ζ-potential, morphology, vesicle bilayer characteristics, physical-chemical stability, and biological efficacy. The obtained results suggest that: (i) niosomes by surfactants in the absence of cholesterol are formed, can entrap CIP, and are stable over time and in artificial biological media; (ii) the CIP inclusion in nanocarriers increase its stability, with respect to free drug; (iii) niosomes preparations were able to induce a relevant inhibition of biofilm formation.